The Mediating Role of Brand Image in the Relationship Between Word of Mouth, Product Quality, and Purchase Decisions of Citra Hand and Body Lotion - Ni Nengah Kariani Kariani; Putu Indah Rahmawati; Komang Endrawan Sumadi Putra (LP2M IAIN Palopo, 2026)
This study aims to examine the effects of word of mouth and product quality on consumers’ purchase decisions regarding Citra hand and body lotion, with brand image serving as a mediating variable. A causal quantitative approach was employed, and data were collected through questionnaires distributed to 110 female respondents residing in Kintamani District. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The findings reveal that word of mouth, product quality, and brand image each have a positive and significant influence on purchase decisions for Citra hand and body lotion. In addition, both word of mouth and product quality significantly contribute to the enhancement of brand image. The results further indicate that brand image partially mediates the relationships between word of mouth and purchase decisions, as well as between product quality and purchase decisions. These findings suggest that favorable consumer recommendations and superior product quality strengthen the brand image of Citra hand and body lotion, which subsequently encourages consumers to make purchasing decisions. Therefore, maintaining product quality and fostering positive word-of-mouth communication are essential strategies for improving brand image and increasing consumer purchase intentions.